Factors affecting nurses' level of job satisfaction in Hospital Universiti Sains Malaysia - Aziz, Nurzaida (2020)
Job satisfaction among nurses will influence the health care services provided as job satisfaction related to job performance. Quality of care given to the patient also associated with the job satisfaction among nurses. A cross sectional study was conducted on 60 respondents. Self- administered questionnaire was given to the respondents that fit the inclusion criteria. The general objective of this study is to determine the factors affecting the level of job satisfaction among nurses in Hospital Universiti Sains Malaysia. In addition, this study was also conducted to determine the association between the socio demographic data (gender, marital status, educational level, age and years of experience), teamwork, intrinsic and extrinsic motivation with the level of job satisfaction among nurses. The data was analysed by descriptive statistics, Fisher exact test and Pearson correlation test using Statistical Package of Social Sciences (SPSS) 24.0. The findings of this study showed that the nurses in Hospital Universiti Sains Malaysia had high level of job satisfaction (n=37, 61.7%), and the remaining had low level of job satisfaction (n=23, 38.3%). In this study, there is no significant association between socio demographic data (gender, marital status, educational level, age and years of experience), teamwork, intrinsic and extrinsic motivation with the level of job satisfaction among nurses in Hospital USM (p > .05). High level of job satisfaction among nurses will ensure a good quality of care to be provided to the patients.